(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
In the article, as we begin to shed light on the radical changes that have taken place in our economic life during the years of independence, let us first recall what kind of economy we have inherited from the old dictatorial regime. During the period of dependence, Uzbekistan could not own its natural resources, land, water, forests and other resources, and could not determine the path of economic development. During the years of independence, they have developed for the better.